Thin Films: On Proton Conductivity in Porous and Dense Yttria Stabilized Zirconia at Low Temperature (Adv. Funct. Mater. 15/2013). (14th April 2013) - Scherrer, Barbara; Schlupp, Meike V.F.; Stender, Dieter; Martynczuk, Julia; Grolig, Jan G.; Ma, Huan; Kocher, Peter; Lippert, Thomas; Prestat, Michel; Gauckler, Ludwig J.
<x xml:space="preserve">Abstract</x> On page 1957 Barbara Scherrer and co‐workers report changes in electrical conductivity at low temperatures that occur when grain size, grain shape, and the porosity of nanoporous zirconiabased thin films are varied. The cover image shows a false‐colored scanning transmission electron microscopy (STEM) image of a yttria stabilized zirconia (YSZ) thin film with a thickness of about 300 nm contacted with platinum. The bright areas within the YSZ thin film are pores, which conduct protons at temperatures below 400 °C. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>